Does Extended Interval Dosing Natalizumab Preserve Effectiveness in Multiple Sclerosis? A 7 Year-Retrospective Observational Study - Riancho, Javier; Setien, Sonia; Sánchez de la Torre, Jose Ramón; Torres-Barquin, Marta; Misiego, Mercedes; Pérez, José Luis; Castillo-Triviño, Tamara; Menéndez-García, Cristina; Delgado-Alvarado, Manuel (Frontiers in Immunology, 2021)
The extended interval dosing (EID) of natalizumab has been suggested to be associated with a reduced risk of progressive multifocal leukoencephalopathy (PML) and short-term preservation of efficacy but its long-term effectiveness remain unknown. We aimed to determine the long-term effectiveness and safety of natalizumab in an EID setting in a cohort of patients with multiple sclerosis (MS) treated for more than 7 years. We conducted an observational retrospective cohort study, including 39 (34 female, 5 male) patients with clinically definite relapsing-MS, initially treated with standard interval dosing (SID) of natalizumab (mean time 54 months [SD29]) who were then switched to EID, every 8 weeks (mean time 76 months [SD13]). The main outcome measures included the following: i)annualized relapse rate(ARR), ii)radiological activity, iii)disability progression, and iv)NEDA-3 no evidence of disease activity index. EID preserved ARR, radiological activity, and prevented disability worsening during follow-up. The proportion of patients maintaining their NEDA-3 status after 24, 48, and 72 months of natalizumab administration in EID was 94%, 73%, and 70%, respectively. Stratified analysis according to history of drug therapy showed that the EID of natalizumab was slightly more effective in naïve patients than in those previously treated with other immunosuppressive drugs. No cases of PML or other severe adverse reactions were reported. In conclusion, long-term therapy with natalizumab in an EID setting following an SID regimen maintained its disease-modifying activity, and was safe and well tolerated for over 7 years. These encouraging observational results need to be confirmed in controlled clinical trials.